The Diagnostic Pitfall of Lymphadenopathy: Ultrasonic Imaging Findings in a Case of Cat Scratch Lymphadenitis - Li Tiantian, Zhu Miao, Shen Dejuan, Qian Xiaoqin (Advanced Ultrasound in Diagnosis and Therapy)
Lymphadenopathy is a common clinical disease, and ultrasonography is its primary preliminary diagnostic screening strategy. With an increase in house-raised pets, the annual incidence of cat scratch lymphadenitis is rising. After infection, the characteristics of the disease include abnormal lymph node enlargement in the local drainage, accompanied by low heat sweats, similar to clinical symptoms of malignant disease. The two-dimensional ultrasound results lack specificity. However, garland-like variation can be observed in the enhanced images, which can be used for the differential diagnosis of cat scratch lymphadenitis. In this case, we obtained the ultrasound and computed tomography images of a patient with cat scratch lymphadenitis and compared and analyzed them with the pathological data.